Reformulating development?: models of indigenous knowledge in international development - Grimm, Carmen (Sociologus, 2017)
Since the second half of the twentieth century, projects of international development have increasingly embraced Indigenous knowledge. This article discusses the ways in which development organisations justify, legitimise, and valorise Indigenous knowledge towards financiers, the general public, and political or developmental institutions. I analyse a development project situated in the Peruvian Andes (region of Ayacucho) which aims at the conservation and transmission of elderly persons’ agricultural knowledge. The project is part of binational development cooperation: Carried out by a Peruvian non-profit organisation, the project is funded by a German non-profit organisation via third-party funds and donations. Based on field research in both Germany and Peru this article shows how the two development organisations frame the same development project in different ways, depending on their respective organisational objectives, relevant discourses, or audiences. Two larger issues are addressed in this paper. Firstly, the meanings that the actors ascribe to Indigenous knowledge differ considerably. In the case of both organisations, Indigenous knowledge is associated with large-scale societal issues. Secondly, the paper asks if and in how far Indigenous knowledge forms the basis of criticism of epistemological power structures in international development.
Gesehen am 18.05.2018